Osteoblasts Promote Prostate Cancer Cell Proliferation Through Androgen Receptor Independent Mechanisms - Ribelli, Giulia; Simonetti, Sonia; Iuliani, Michele; Rossi, Elisabetta; Vincenzi, Bruno; Tonini, Giuseppe; Pantano, Francesco; Santini, Daniele (Frontiers in Oncology, 2021)
Patients with metastatic prostate cancer frequently develop bone metastases that elicit significant skeletal morbidity and increased mortality. The high tropism of prostate cancer cells for bone and their tendency to induce the osteoblastic-like phenotype is a result of a complex interplay between tumor cells and osteoblasts. Despite the role of osteoblasts in supporting prostate cancer cell proliferation has been reported by previous studies, their precise contribution in tumor growth remains to be fully elucidate. Here, we tried to dissect the molecular signaling underlining the interactions between castration resistant prostate cancer (CRPC) cells and osteoblasts using in vitro co-culture models. Transcriptomic analysis showed that osteoblast conditioned media (OCM) induced the overexpression of genes related to cell cycle in CRPC cell line, C4-2B, but, surprisingly, reduced androgen receptor (AR) transcript levels. In-depth analysis of AR expression in C4-2B cells after OCM treatment showed an AR reduction at mRNA (p= 0.0047), protein (p= 0.0247) and functional level (p= 0.0029) and, concomitantly, an increase of C4-2B cells in S-G2-M cell cycle phases (p= 0.0185). An extensive proteomic analysis revealed in OCM the presence of some molecules that reduced AR activation and, among these, Matrix metalloproteinase-1 (MMP-1) was the only able to block AR function (0,1 ng/ml p= 0.006; 1 ng/ml p= 0.002; 10 ng/ml p= 0.0001) and, at the same time, enhance CRPC proliferation (1 ng/ml p= 0.009; 10 ng/ml p= 0.033). Although the increase of C4-2B cell growth induced by MMP-1 did not reach the proliferation levels observed after OCM treatment, the adding of Vorapaxar, a MMP-1 receptor inhibitor (Protease-activated receptor-1, PAR-1), significantly reduced C4-2B cell cycle (0,1 μM p= 0.014; 1 μM p= 0.0087). Overall, our results provide a novel AR-independent mechanism of CRPC proliferation and suggest that MMP-1/PAR-1 could be one of the potential pathways involved in this process.